Implementation of Project-Based Learning Model Based on STEM Design Thinking and Its Effecton toward Critical Thinking Skills of Elementary School Students - Wulandari, Adelia; Yektyastuti, Resti; Erlangga, Sony Yunior; Effane, Anne (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Critical thinking skills are essential in assisting students in the learning process, especially in today's 21st century. STEM design thinking based project-based learning is a learning model that can improve critical thinking skills. The purpose of this study is to determine whether there is an influence of the STEM design thinking-based project-based learning model on the critical thinking skills of grade V elementary school students. This study used to a quasi-experimental research approach with a posttest only design. The subjects in this study were grade 5th students of SDN Sentul 03, Babakan Madang district, Bogor, West Java, consisting of 91 students. The way to collect data used is observation, question and answer and recording, with research measuring tools in the form of tests. The hypothesis test used is a t-test to test the level of significance of the influence of the independent variable on the dependent variable. Based on the results of the analysis, it can be seen that the results of the independent sample t-test obtained significance results of 0.000 < 0.05. The data shows that there is an influence of the use of project-based learning models based on STEM design thinking on the critical thinking skills of grade 5th students of SDN Sentul 03.